Identification and management of adverse effects of antipsychotics in a tertiary care teaching hospital - Jisha Myalil Lucca; Ramesh Madhan; Gurumurthy Parthasarathi; Dushad Ram (Wolters Kluwer Medknow Publications, 2014)
Objective: Antipsychotics have revolutionized psychiatry by allowing significant numbers of patients in long-term hospital settings to be discharged and successfully maintained in the community. However, these medications are also associated with a range of adverse events ranging from mostly annoying to rarely dangerous. This study is carried out to identify the adverse drug reactions (ADRs) to antipsychotics and its management in psychiatric patients. Methods: Prospective interventional study was conducted in the psychiatric unit of a tertiary care hospital. Patients of any age and either sex prescribed with at least one antipsychotic were included and monitored for ADRs. Findings: Among the 517 patients receiving antipsychotics, a total of 289 ADRs were identified from 217 patients at an overall incidence rate of 41.97%. Sixty-seven different kinds of ADRs were observed in the study patients. Central and peripheral nervous system was the most commonly affected system organ class (n = 59) and weight gain (n = 30) was the most commonly observed ADR. Olanzapine was most commonly implicated in reported ADRs (n = 92) followed by risperidone (n = 59). Of the 289 ADRs, 80% required interventions including cessation of drug and/or specific/symptomatic/nonpharmacological treatment. Conclusion: This post marketing surveillance study provides a representative data of the ADR profile of the antipsychotics likely to be encountered in psychiatric patients in an Indian tertiary care hospital.